2020
DOI: 10.1038/s41598-020-76431-5
|View full text |Cite
|
Sign up to set email alerts
|

Memory-driven capture occurs for individual features of an object

Abstract: Items held in working memory (WM) capture attention (memory-driven capture). People can selectively prioritize specific object features in WM. Here, we examined whether feature-specific prioritization within WM modulates memory-driven capture. In Experiment 1, after remembering the color and orientation of a triangle, participants were instructed, via retro-cue, whether the color, the orientation, or both features were relevant. To measure capture, we asked participants to execute a subsequent search task, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
2
9
0
2
Order By: Relevance
“…On the other hand, information voluntarily activated in WM can guide external selection (Gazzaley & Nobre, 2012 ; Wolfe, 2021 ; Wolfe & Horowitz, 2004 ). These findings are consistent with the idea that attention and memory are intertwined processes, supporting each other in a reciprocal fashion (Olivers et al, 2011 ; Sasin & Fougnie, 2020 ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, information voluntarily activated in WM can guide external selection (Gazzaley & Nobre, 2012 ; Wolfe, 2021 ; Wolfe & Horowitz, 2004 ). These findings are consistent with the idea that attention and memory are intertwined processes, supporting each other in a reciprocal fashion (Olivers et al, 2011 ; Sasin & Fougnie, 2020 ).…”
supporting
confidence: 90%
“…Thus, an exploration of whether WM capture is improved by training can help to constrain theoretical frameworks by better understanding the rigidness or flexibility of attentional capture. Moreover, previous studies showed that allowing participants to drop information from memory results in reduced capture if that information is used as search distractors (Sasin & Fougnie, 2020 ; Sasin et al, 2017 ). Importantly, the instruction to remove an item from memory may reduce but not eliminate capture (Sasin et al, 2017 ; but see Olivers et al, 2006 ).…”
mentioning
confidence: 99%
“…Furthermore, if selecting a visual feature from an object stored in working memory also involved motor planning (or the selection of an associated motor code), we should observe stronger suppression of oscillatory mu and beta power with an estimated source in the premotor cortex contralateral (but not ipsilateral) to the to-be-executed response for the selective cue conditions relative to the neutral condition. This effect should occur together with a stronger suppression of alpha power over posterior visual areas following the selective cues that was already observed in the context of the retrospective selection of visual object features (see Hajonides et al, 2020;Niklaus et al, 2017;Sasin & Fougnie, 2020;Ye et al, 2016).…”
mentioning
confidence: 67%
“…For objects with more than a single feature, the precision of individual features may improve through dimension-specific retro-cueing (Heuer & Schubö, 2017; Niklaus et al, 2017; Park et al, 2017; Ye et al, 2016). As a consequence, memory-based attentional capture may increase for the cued feature (Sasin & Fougnie, 2020). Conversely, it may also be possible to decrease the priority of representations in memory according to the relevance for the experimental task.…”
Section: Discussionmentioning
confidence: 99%